Design, fabrication and characterization of titanium with graded porosity by using space-holder technique (2014)
ABSTRACT: Bone resorption and further failure of titanium implants are often associated to stress-shielding phenomenon. This problem of mechanical incompatibility is even worst due to anisotropy of bone tissue to be replaced. In this work, different samples with gradient longitudinal porosity by using space-holder technique were fabricated and characterized. Main results of this work indicated that: 1) Experimental procedure for space-holder elimination was effective, feasible and reproducible, with better results for a compaction pressure of 800 MPa, and for highest salt contents; 2) 3-D images by micro-CT and images analysis of optical micrographs showed that initial designs were reasonably repeatable; this was observed in terms of both porosity and interfaces quality; and 3) Designs of 30/40/50 and 30/50/30, allowed to solve stress shielding without any important effect on mechanical strength, from the cortical bone point of view.